Analisis Kritis Konsep Penanaman Akidah Anak Usia Dini Menurut Pemikiran Imam Al-Ghazali dan Implementasinya pada Pendidikan Islam Modern - Darul Mustofa; Desta Tri Wahyuni; Erlina; Fahrul Ghazi; Idham Kholid (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research critically examines Imam Al-Ghazali’s concept of faith (ʿaqīdah) formation in early childhood and its relevance within modern Islamic education. Employing a qualitative-descriptive approach through a critical literature review, this study explores Al-Ghazali’s seminal works—Ihya’ ‘Ulum al-Din and Ayyuha al-Walad—and compares them with contemporary Islamic educational theories. The analysis indicates that Al-Ghazali emphasized moral exemplarity, consistent worship practice, spiritual self-awareness (muraqabah), and purification of the soul (tazkiyah al-nafs) as foundational pillars of a child’s faith formation. These principles remain highly applicable to modern Islamic education when integrated with contextual, experiential, and character-based pedagogies. The synthesis of Al-Ghazali’s classical thought with current educational innovations presents a sustainable framework for cultivating faith-based character among young learners in the digital era.